Biocompatible Mesoporous Silica–Polydopamine Nanocomplexes as MR/Fluorescence Imaging Agent for Light-Activated Photothermal–Photodynamic Cancer Therapy In Vivo - Lu, Jiahui; Ni, Chen; Huang, Jie; Liu, Yawen; Tao, Yingkai; Hu, Pengcheng; Wang, Yong; Zheng, Shaohui; Shi, Meilin (Frontiers in Bioengineering and Biotechnology, 2021)
Conventional cancer mono-phototherapy suffers from low therapeutic efficacy and undesired post-treatment damage for adjacent normal tissues. Therefore, the lower NIR laser irradiation power is vital to the reduction or preclusion of risk of scalds and burns in normal tissues. Herein, we rationally proposed a novel multifunctional nanocomplex, which enabled good magnetic resonance (MR) imaging contrast effect and promising photothermal conversion efficacy. The prepared core/shell nanocomplexes (MSN-Ce6@PDA(Mn)) were composed of chlorin e6 embedded mesoporous silica/nanoparticle composites as the cores for photodynamic therapy. Subsequently polydopamine and manganese ions were conjugated on the above-mentioned cores as the shell, to realize the MR imaging modality. With the guidance of MR and fluorescence imaging, these MSN-Ce6@PDA(Mn) particles primarily accumulated in MDA-MB-231 tumors via EPR effect. The prepared MSN-Ce6@PDA(Mn) exhibited several unique features: (1) covalent bonding of potent hydrophobic photosensitizers Ce6 to MSN@PDA core-shell nanocarrier can improve the stability of Ce6, rendering its application for fluorescence imaging and photodynamic therapy in vivo; (2) the in vivo magnetic resonance imaging capability of PDA(Mn) shell provides a good information for the visual study of tissue distribution as well as guidance to MSN-Ce6@PDA(Mn) regimen; (3) the therapeutic effect of MSN-Ce6@PDA(Mn) can be further enhanced under irradiation of dual wavelengths. Therefore, given the combination of the aforementioned advantages with its excellent biosafety, the MSN-Ce6@PDA(Mn) nanocomplex demonstrates significant therapeutic effects. This study promoted the development of multi-functional nanoplatforms for tumor diagnosis and therapy.